Formação inicial de professores de Matemática no âmbito das tecnologias digitais de informação e comunicação - TDICS - Dalla Nora, Marcia (Universidade do Vale do Rio dos Sinos, 2020)
The present thesis has as objective to analyze in which way the Mathmatics course graduates act with the TDICS, from their initial training, in teaching internship. For this research, were carried out focus groups with graduate- internships of the Mathmatics degree course of a Community University located in north of RS, South region of the country, in line with the documents of the curriculum which also form empirical material of this thesis. The results are verified having as inspiration Foucalt speech analyze and its commentators. For that, I examined the legal documents, the pedagogical project – PPC – of Mathmatics degree of a University located in north of RS, South region of the country, Resolutions and Report of National Curriculum Guidelines – CNE – and the Common National Curriculum Base – BNCC – of Mathmatics area ( final grades of Elementary School and High School ), besides four focus groups with graduate internships of Mathmatics degree course. So, during and after the transcription of focus groups and the study of documents, I analyzed how the TDICS are producing other processes in the contemporary, considering the passage of graduate internships formation, focusing on performance of internships in classroom, examining the inserction and use of TDICS, that influence and, mainly change our lives, and understanding the role of Mathmatics teacher in this process in which people are using technology in Science in this contemporary society. From that, I could point out some enunciative regularities, that led me to create two dimensions of analysis: 1º) salvationist speech, and, at the same time, inequality of access and dispersal in dealing with the TDICS on internship carrying out, and 2º) teaching posture and the TDICS. When I discuss the first dimension, I bring how much, many times, the inserction of TDICS in school environment is naturalized and with a salvationist tone, in realities with inequality of access and the lack of attention caused by advance of TDICS in schools. Regarding the second dimension, the teaching posture of the graduate internships in this meeting with the school on the internship.
Keywords: TDICS; Escola; Formação Inicial de Professores de Matemática; Desigualdade; Postura docente; School; Initial formation of Mathematics teachers; Teaching posture; ACCNPQ::Ciências Humanas::Educação